Students' perception of pre-exposure prophylaxis as a prevention strategy for reducing HIV/AIDS incidences at Rhodes University - Lepelesana, Mamorena Sylvia (Rhodes University, Faculty of Humanities, Department of Sociology)
South Africa has the largest number of people living with HIV/AIDS compared to the rest of the world, with young people most at risk. The World Health Organisation (WHO) recommends the use of Pre-Exposure Prophylaxis (PrEP) in key populations at a higher risk of exposure to HIV/AIDS. The HIV/AIDS pandemic remains a pressing issue among higher education institutions, with a need for a comprehensive understanding of barriers and facilitators associated with the use of PrEP. The Higher Education AIDS (HEAIDS) plays a pivotal role in the mitigation of the spread of HIV/AIDS in Higher Education Institutions (HEIs). In this study, Rhodes University serves as a focal point for exploring PrEP implementation and acceptance. This qualitative study examines Rhodes University students' PrEP knowledge, perception, practice, and roll-out preference. More evidence is required to measure progress among students. A study was conducted involving sixteen (16) in-depth semi-structured interviews with students and health care workers, as well as a focus group consisting of three (3) students aged between 20-60 years. This study used the Socio-Ecological Model and Health Belief Model as theoretical frameworks. Participants in the study identified both the barriers and the facilitators to the use of PrEP. The findings show that there is a lack of knowledge and low perception among students about PrEP. The study found that lack of knowledge was the source of the stigma and misconception about PrEP. Most participants expressed the need for more information to differentiate between the ARVs in PrEP and the ARV medication for HIV-positive people. However, they further expressed a willingness to embrace PrEP if they had information about it. The study highlights that the use of PrEP is linked to individual and environmental factors, which are crucial for PrEP roll-out. These factors include access to PrEP in a friendly manner, supportive family and friends, and the reduction of stigma and misconception. Therefore, when addressed, the said factors can foster the use of PrEP and mitigate barriers. For students to fully realise the benefits of HIV/AIDS prevention strategies like PrEP, there is a need for informed educational efforts. A well-informed student body is important for the successful adoption and use of PrEP. The findings suggest that the health care workers were knowledgeable and conscious about the use of PrEP. However, there were inconsistencies in the information provided by the health care workers regarding the recommended period for taking PrEP before testing again and taking the three-month course. The inconsistencies raise questions regarding the accuracy and reliability of the information provided.
Keywords: Pre-exposure prophylaxis; HIV infections; AIDS (Disease); College students -- Attitudes; Stigma (Social psychology); Rhodes University